2004
DOI: 10.1002/chin.200422224
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and Antiinflammatory Activities Evaluation of (‐)‐O‐Acetyl, (‐)‐O‐Methyl, (‐)‐O‐Dimethylethylamine Cubebin and Their Preparation from (‐)‐Cubebin.

Abstract: O-Dimethylethylamine Cubebin and Their Preparation from (-)-Cubebin. -The anti-inflammatory and antinociceptive effects of the cubebin derivatives (I) are investigated using different animal models. Overall, the results show that the acylation and amination of cubebin are efficient in enhancing its analgesic activity, as well as its anti-inflammatory activity. -(SOUZA, G. H. B.; DA SILVA FILHO, A. A.; DE SOUZA, V. A.; PEREIRA, A. C.; DE A. ROYO, V.; E SILVA, M. L. A.; DA SILVA, R.; DONATE, P. M.; CARVALHO, J. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Considering its biological activities, Bastos et al (2001) reported antiinflammatory and analgesic effects of (-)-cubebin in rats and Coimbra et al (2004) observed that its derivate (-)-o-benzylcubebin showed only analgesic activity. Souza et al (2004) showed that acetylated (-)-cubebin presented more effective anti-inflammatory activity than (-)-cubebin and acetylated and aminated derivatives of (-)-cubebin showed more analgesic effects. Bastos et al (1999) and Souza et al (2005) reported significant trypanocidal activity of derivatives of (-)-cubebin.…”
Section: Introductionmentioning
confidence: 99%
“…Considering its biological activities, Bastos et al (2001) reported antiinflammatory and analgesic effects of (-)-cubebin in rats and Coimbra et al (2004) observed that its derivate (-)-o-benzylcubebin showed only analgesic activity. Souza et al (2004) showed that acetylated (-)-cubebin presented more effective anti-inflammatory activity than (-)-cubebin and acetylated and aminated derivatives of (-)-cubebin showed more analgesic effects. Bastos et al (1999) and Souza et al (2005) reported significant trypanocidal activity of derivatives of (-)-cubebin.…”
Section: Introductionmentioning
confidence: 99%
“…This may be partially explained by the high specificity of acetylated anti-inflammatory compounds (Souza et al, 2004), such as aspirin, which inhibit prostaglandin synthesis by inactivating COX. Aspirin selectively acetylates the hydroxyl group of a serine residue (Ser 53), among the terminal 70 amino acids of the PGEs enzyme chains.…”
Section: Discussionmentioning
confidence: 99%
“…1). Lignans, one of the longest known classes of natural products, have attracted much interest over the years on account of their broad range of biological activities, such as antileishmanial (Barata et al, 2000), antimalarial (Zhang et al, 2001), antitumor (Bastos et al, 1996), and anti-inflammatory (Souza et al, 2004) activities, among others. Recently, our group reported the significant trypanocidal and antileishmanial activities of dibenzylbutyrolactone lignans (Souza et al, 2005;Royo et al, 2003;Bastos et al, 1999).…”
Section: Introductionmentioning
confidence: 99%